3D finite-element modeling of air-cell-based cushions and buttock tissues during prolonged sitting. (March 2022) - Yu, Chenhao; Sacris, Joel Martin; Gai, Yan; Lei, Chi Hou
Abstract: Introduction: Prolonged sitting can lead to serious health issues. Patients with spinal cord injuries may even develop pressure ulcers as stress accumulates on the ischial tuberosity. Air-cell-based (ACB) cushions have been shown to reduce tissue stress and help mitigate the effects of chronic sitting. Meanwhile, finite-element simulations have been implemented for different patient conditions. However, existing models are mostly two-dimensional with unrealistic simplifications. Methods: A realistic three-dimensional multi-physics model with fewer artificial assumptions is presented. A commercial ACB cushion and an emulational buttock consisting of an actual hip bone and soft tissue (muscle, fat, and skin layers) were considered. Computational Fluid Dynamics and Transient Structural Analysis using ANSYS were utilized to simulate the ACB cushion during expansion and buttock tissue during sitting. Results: Profile of airflow and pressure distributions caused by the airflow within the ACB cushion were computed when the air was pumped into the cells. Expansion of the ACB cushion was simulated, and an optimal inner pressure range (100–500 Pa) was determined. The human buttock sitting on the cushion was then simulated and visualized. Conclusions: The realistic three-dimensional model can accurately capture deformation and stress profiles pertinent to sitting on an ACB cushion. The model allows us to optimize the ACB cushions and operating conditions missing in previous studies. The model has also resolved several weaknesses in former models, such as the artificial air layers between air cells and unrealistically imposed internal pressure. Graphical abstract: Image 1 Highlights: A realistic three-dimension model of ACB cushion and buttock during sitting was studied with finite element analysis. Fluid-structure interaction linking computational fluid dynamics and transient structural analysis was utilized. The model eliminated infeasible conditions adopted by previous works. Airflow pumped into air cells was simulated, and an optimal operating pressure for cushion and human body was predicted. More accurate simulation results were obtained during sitting than in previous works.